2012
DOI: 10.1111/j.1365-294x.2012.05678.x
|View full text |Cite
|
Sign up to set email alerts
|

Genetic basis of local adaptation and flowering time variation in Arabidopsis lyrata

Abstract: Understanding how genetic variation at individual loci contributes to adaptation of populations to different local environments is an important topic in modern evolutionary biology. To date, most evidence has pointed to conditionally neutral quantitative trait loci (QTL) showing fitness effects only in some environments, while there has been less evidence for single-locus fitness trade-offs. At QTL underlying local adaptation, alleles from the local population are expected to show a fitness advantage. Cytoplas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

7
101
0
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 89 publications
(109 citation statements)
references
References 67 publications
7
101
0
1
Order By: Relevance
“…QTL for flowering time in Norway were detected on LG1 and LG3, with the former coinciding with the LG1 resource allocation QTL detected in North Carolina ( Figure 8C; Leinonen et al 2013). In both cases, Norway alleles contributed additively to earlier flowering, consistent with the population differences detected in Norway (Leinonen et al 2013).Two QTL regions, on LG1 and LG8, explained much of the cumulative survival variation in each year following the first reproductive season ( Figure 8D; Leinonen et al 2013). These regions corresponded to the LG1 and LG8 resource allocation QTL regions in North Carolina.…”
mentioning
confidence: 75%
“…QTL for flowering time in Norway were detected on LG1 and LG3, with the former coinciding with the LG1 resource allocation QTL detected in North Carolina ( Figure 8C; Leinonen et al 2013). In both cases, Norway alleles contributed additively to earlier flowering, consistent with the population differences detected in Norway (Leinonen et al 2013).Two QTL regions, on LG1 and LG8, explained much of the cumulative survival variation in each year following the first reproductive season ( Figure 8D; Leinonen et al 2013). These regions corresponded to the LG1 and LG8 resource allocation QTL regions in North Carolina.…”
mentioning
confidence: 75%
“…In conclusion, early life stages are known to be under strong selection (15)(16)(17)(18)(19) and to have cascading effects across the whole life cycle (16,20,21), but they are seldom included in studies on the genetic basis of local adaptation (12)(13)(14)(22)(23)(24)(25)(26)(27)(28). By conducting a reciprocal transplant experiment including the whole life cycle and maternal effects, we have shown that selection during early life stages contributes strongly to both the magnitude and the genetic basis of adaptive differentiation among natural populations of A. thaliana.…”
Section: Discussionmentioning
confidence: 99%
“…The remaining seedling was monitored until fruit maturation. At fruit maturation (April [26][27][28]2013 in Italy, June 24-26, 2013 in Sweden), we recorded the survival (from the moment of thinning of established seedlings until fruit maturation) and fecundity (number of fruits containing viable seeds) of surviving plants. We calculated total fitness as the number of fruits produced per planted viable seed (establishment × survival × fecundity), using the focal plant as a proxy for the survival and fecundity of removed seedlings.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…To appreciate the effects of environmental heterogeneity on the evolution of quantitative traits, we must link classical quantitative genetics to ecology using manipulative experiments in realistic natural settings. Field studies can uncover novel functions of previously characterized genes (Brock et al, 2009), examine how divergent selection contributes to local adaptation at the organismal level (Hall and Willis, 2006), address the genetic basis of adaptive population differentiation (Leinonen et al, 2013), expose genetic correlations among traits that could constrain adaptation (Brock et al, 2009) and reveal whether genetic variation is sufficient to enable evolutionary responses to selection imposed by anthropogenic disturbance (Etterson and Shaw, 2001).…”
Section: Introductionmentioning
confidence: 99%